2022
DOI: 10.21203/rs.3.rs-1835449/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Size characterization of Plasmonic Nanoparticles with Dark-Field Single Particle Spectrophotometry

Abstract: Plasmonic nanoparticles are widely used in multiple scientific and industrial applications. Although many synthesis methods have been reported in the literature throughout the last decade, controlling the size and shape of large populations still remains as a challenge. As size and shape variations have a strong impact in their plasmonic properties, the need to have metrological techniques to accurately characterize their morphological features is peremptory. We present a new optical method referred as Dark-Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Commercial biomedical devices utilizing nanomaterials are currently commonplace, and their dimensional parameters play a signifcant role in determining their efect, property, and performance. Electron microscopy, still one of the main available analyzing techniques used to characterize and study nanoparticles [56], is considered the widely and preferable used metrological system in laboratories for characterizing the dimensional properties of nanoparticles due to its higher nanometric resolution that allows accurate measurement of nanometric scale structures; however, sample preparation procedures remain a keystone [57][58][59]. Te present study showed that nanoparticle dimensions of Nb and Ta coatings were comparable and nearly half of V coatings, which may refect their efect on the tribological behavior since both of them reduce the friction of their SS substrate nearly to half, while V coatings did not impact the coefcient of friction of their SS substrate positively, which may be attributed to the capability of smaller nanoparticles to form a triboflm with stronger intrinsic mechanical properties or due to an increase in the ability of the nanoparticles passing through the contact, hence improving the tribological behavior of Nb and Ta coatings, coincided with Buranich et al [60], Liu et al, [61], and Bhimaraj et al [62], but in contrast to Zou et al [63], who reported in their study that 30% of friction reduction may be gained by increasing nanoparticle size.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial biomedical devices utilizing nanomaterials are currently commonplace, and their dimensional parameters play a signifcant role in determining their efect, property, and performance. Electron microscopy, still one of the main available analyzing techniques used to characterize and study nanoparticles [56], is considered the widely and preferable used metrological system in laboratories for characterizing the dimensional properties of nanoparticles due to its higher nanometric resolution that allows accurate measurement of nanometric scale structures; however, sample preparation procedures remain a keystone [57][58][59]. Te present study showed that nanoparticle dimensions of Nb and Ta coatings were comparable and nearly half of V coatings, which may refect their efect on the tribological behavior since both of them reduce the friction of their SS substrate nearly to half, while V coatings did not impact the coefcient of friction of their SS substrate positively, which may be attributed to the capability of smaller nanoparticles to form a triboflm with stronger intrinsic mechanical properties or due to an increase in the ability of the nanoparticles passing through the contact, hence improving the tribological behavior of Nb and Ta coatings, coincided with Buranich et al [60], Liu et al, [61], and Bhimaraj et al [62], but in contrast to Zou et al [63], who reported in their study that 30% of friction reduction may be gained by increasing nanoparticle size.…”
Section: Discussionmentioning
confidence: 99%